Effects of Health Literacy Intervention on Health Literacy Level and Glucolipid Metabolism of Diabetic Patients in Mainland China: A Systematic Review and Meta-Analysis - Yangli Chen; Xue Ran; Yalan Chen; Kui Jiang (Journal of Diabetes Research)
Objective. To systematically evaluate the effects of health literacy intervention on health literacy level and glycolipid metabolism of people with diabetes in mainland China. Methods. A systematic review of journal articles discussing diabetes and health literacy was performed by searching PubMed, Embase, the Science Citation Index Expanded (SCIE) database of Web of Science, the China National Knowledge Infrastructure (CNKI) database, the Chinese Scientific and Technical Journals database (CQVIP), and the Wanfang database. Cochrane Effective Practice and Organization of Care Review Group (EPOC) standards were applied for quality assessment. A meta-analysis was performed using Stata 12.0 software. Results. A total of 44 articles, including seven controlled before-and-after trials (CBAs), 27 randomized controlled trials (RCTs), and 10 nonrandomized controlled trials (non-RCTs), were included. The results showed that (1) health literacy level in the intervention group was improved compared with the preintervention and the control group; (2) fasting plasma glucose (FPG) (standardized mean difference SMD=−1.85, 95% CI: −2.28, −1.42), 2-hour plasma glucose (2hPG) (SMD=−2.18, 95% CI: −2.68, −1.68), and HbA1c (weighted mean difference WMD=−1.21, 95% CI: −1.48, −0.94) were significantly reduced in the intervention group; (3) total cholesterol (TC) (WMD=−0.43, 95% CI: −0.64, −0.23) was significantly reduced in the intervention group, although there were no statistically significant differences for triglycerides (TG) (WMD=−0.34, 95% CI: −0.73, 0.05), low-density lipoprotein cholesterol (LDL-C) (WMD=−0.20, 95% CI: −0.46, 0.07), or high-density lipoprotein cholesterol (HDL-C) (WMD=−0.06, 95% CI: −0.29, 0.17). Conclusion. Intervention based on health literacy can effectively improve health literacy levels and reduce glucose metabolism and TC level among people with diabetes mellitus, although it has no significant effect on TG, LDL-C, or HDL-C.